PENGARUH LEADER MEMBER EXCHANGE TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK ACEH SYARIAH CABANG BIREUEN DENGAN KOMITMEN ORGANISASI DAN PERCEIVED ORGANIZATIONAL SUPPORT SEBAGAI VARIABEL INTERVENING - Sulaiman Sulaiman; Razali Razali (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
This research aimed to examine the influence of employee leader member exchange toward job satisfaction and to examine the mediation effect of commitment of organizations and perceived organizational support. The sample of this research was 108 employee of PT. Bank Aceh Syariah Cabang Bireuen. The tool of data analysis was Path analysis with the method of SEM (Structural Equation Modeling) by using Amos. The result of this research showed that leader member exchange, commitment of organizations, and perceived organizational support positively and significantly influenced employee job satisfaction. commitment of organizations, and perceived organizational support perfect/fully mediated the exogenous and endogenous variables. Keywords: Leader Member Exchange, Commitment of Organizations, Perceived Organizational Support, and Employee Job Satisfaction